XVI. YÜZYIL DİVAN ŞAİRLERİNDEN FUZULİ'NİN FELSEFİ DÜŞÜNCELERİ - İPEK, FATİH (Fırat Üniveristesi, 2008)
Edebiyatımızın büyük şairlerinin başında gelen Fuzuli, edebiyatımızda olduğu kadar İslam düşünce tarihinde de önemli bir yere sahiptir. Fuzuli mensur eserlerinde ve şiirlerinde felsefenin birçok önemli meselesini ele almıştır. Bizde bu çalışmamızda onun varlık, bilgi ve ahlak alanındaki görüşlerini incelemeye çalışacağız.

Fuzuli,one of the foregoing poets of our literature has an important place not only in literature but also in the history of İslamic thought.In his prose and poems,fuzuli handled many important issues of philosopy.In this work,we will try to deal with his views about existence, knowladge, and moral.
The philosophical thoughts of fuzûli who is among the poets of clasiccal ottoman poetry in 16th century
Keywords: Din; Felsefe